An Adaptor Role for Cytoplasmic Sam68 in Modulating Src Activity during Cell Polarization - Huot, Marc-Étienne (American Society for Microbiology (ASM), 2009)
The Src-associated substrate during mitosis with a molecular mass of 68 kDa (Sam68) is predominantly nuclear and is known to associate with proteins containing the Src homology 3 (SH3) and SH2 domains. Although Sam68 is a Src substrate, little is known about the signaling pathway that link them. Src is known to be activated transiently after cell spreading, where it modulates the activity of small Rho GTPases. Herein we report that Sam68-deficient cells exhibit loss of cell polarity and cell migration. Interestingly, Sam68-deficient cells exhibited sustained Src activity after cell attachment, resulting in the constitutive tyrosine phosphorylation and activation of p190RhoGAP and its association with p120rasGAP. Consistently, we observed that Sam68-deficient cells exhibited deregulated RhoA and Rac1 activity. By using total internal reflection fluorescence microscopy, we observed Sam68 near the plasma membrane after cell attachment coinciding with phosphorylation of its C-terminal tyrosines and association with Csk. These findings show that Sam68 localizes near the plasma membrane during cell attachment and serves as an adaptor protein to modulate Src activity for proper signaling to small Rho GTPases.